2018
DOI: 10.1002/ppul.23945
|View full text |Cite
|
Sign up to set email alerts
|

Nebulized hypertonic saline in infants hospitalized with moderately severe bronchiolitis due to RSV infection: A multicenter randomized controlled trial

Abstract: Nebulized HS therapy did not significantly reduce LOS among infants with bronchiolitis due to RSV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 47 publications
1
33
0
Order By: Relevance
“…The mean (±SD) length of stay (LOS) in hospital was quite similar in the HS (4.81 ± 2.14 days) and NS (4.61 ± 2.18 days) groups. The duration of oxygen administration and the improvement of clinical severity scores from baseline to 72 h showed no significant differences between the treatment groups . The negative result of the study that is no association between saline inhalations and recovery from bronchiolitis was confirmed with survival and multivariate analyses.…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…The mean (±SD) length of stay (LOS) in hospital was quite similar in the HS (4.81 ± 2.14 days) and NS (4.61 ± 2.18 days) groups. The duration of oxygen administration and the improvement of clinical severity scores from baseline to 72 h showed no significant differences between the treatment groups . The negative result of the study that is no association between saline inhalations and recovery from bronchiolitis was confirmed with survival and multivariate analyses.…”
mentioning
confidence: 76%
“…The negative result of the study that is no association between saline inhalations and recovery from bronchiolitis was confirmed with survival and multivariate analyses. The conclusions were similarly negative in ad hoc subgroup analyses performed between groups constructed on the basis of disease severity …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, a more recent RCT by Morikawa et al . failed to detect a difference in LOS between HS and NS …”
Section: Discussionmentioning
confidence: 96%
“…A meta‐analysis carried out by Zhang et al suggested that when used in the emergency department setting in combination with bronchodilators, inhaled hypertonic saline may help reduce the risk for the hospital admission. However, Morikawa et al reported results of an open‐label multicenter randomized controlled trial comparing outcomes in 128 infants hospitalized with RSV bronchiolitis treated with either 3% hypertonic saline or normal saline and found no effect on length of hospital stay.…”
Section: Introductionmentioning
confidence: 99%